ANALISIS FAKTOR KESELAMATAN LINGKUNGAN BELAJAR DAN BERMAIN UNTUK ANAK DI RPTRA SUNTER JAYA BERSERI - Rembulan, Glisina Dwinoor (Jurnal Pengabdian dan Kewirausahaan, 2020)
The safety factor of learning and playing environment in the children's playground at the Sunter Jaya Berseri RPTRA is one thing that needs attention, because they can provide benefits in supporting children's learning and play activities. Good play facilities must be designed safely and comfortably so as not to pose a potential hazard to children. With the presence of play and learning facilities there is a continuous interaction between humans and their environment. Through a play approach, children can develop psychological and physical aspects. Development of psychological and physical aspects can be supported by outdoor play facilities. This self-safety education seminar on children's learning and playing environments is one of the preventive efforts to reduce accidents in the children's play environment, especially in the Sunter Jaya Berseri RPTRA. The aim is to provide understanding to Sunter Jaya Berseri's RPTRA managers and administrators about the dangers and how to avoid them. Keywords: safety, learning, playing, children